Consumer understanding of sugars claims on food and drink products - Patterson, N J (Blackwell Publishing Ltd, 2012)
Consumer understanding of nutrition and health claims is a key aspect of current regulations in the European Union (EU). In view of this, qualitative and quantitative research techniques were used to investigate consumer awareness and understanding of product claims in the UK, focusing particularly on nutrition claims relating to sugars. Both research methods identified a good awareness of product claims. No added sugars claims were generally preferred to reduced sugars claims, and there was a general assumption that sweeteners and other ingredients would be added in place of sugars. However, there was little awareness of the level of sugar reduction and the associated calorie reduction in products when reduced sugars claims were made on pack. In focus groups, participants felt deceived if sugar reduction claims were being made without a significant reduction in calories. This was reinforced in the quantitative research which showed that respondents expected a similar and meaningful level of calorie reduction to the level of sugar reduction. The research also identified consumer confusion around the calorie content of different nutrients, including over-estimation of the calorie content of sugars. This is crucial to consumers' expectations as they clearly link sugar to calories and therefore expect a reduction in sugar content to deliver a reduction in calorie content.